Effects of Breakfast Omission on Resting, Exercise, and Postexercise Autonomic and Hemodynamic Profile in Men. Issue 2 (3rd April 2022) - Barbosa, Enoque; Pereira, Raiane Maiara dos Santos; Guaraná, Weslayne Lima; Rocha, Caio Gabriel de Jesus; Fernandes, Pedro Henrique; de Oliveira, Pedro Henrique Lobato; Molina, Guilherme E.; da Cruz, Carlos Janssen Gomes
ABSTRACT: Purpose : The acute effects of fasting interventions on metabolic dynamics have been widely investigated. However, knowledge about the acute effect of overnight fasting on hemodynamic and cardiac autonomic modulation is limited, especially during and after exercise. Our objective was to investigate the effects of breakfast omission on hemodynamic and cardiac autonomic modulation during different stress conditions. Method : Twenty-one young men [age: 20.3 (20.1, 26.5 years); body mass index: 22.7 (21.4, 24.4 kg/m 2 )] underwent resting and postexercise blood pressure assessments and heart rate variability (HRV) analysis, using the SD1 and SD2 indices of Poincaré plots, at rest in supine and standing positions, every 10 minutes during moderate cardiorespiratory training and every 10 minutes throughout the postexercise recovery phase, for a total of 30 minutes for each phase (exercise and recovery). All measurements were performed in a randomized order after overnight fasting or 60 minutes after a breakfast containing ~20% of the total recommended daily calories. The normality hypothesis was rejected, and the Wilcoxon test was conducted to compare the interventions ( p < .05). Results : No differences between interventions were observed for resting and postexercise blood pressures ( p = .21 to 0.87) or for resting, exercise, and postexercise SD1 ( p = .10 to 0.82) and SD2 indices ( p = .14 to 0.71). Conclusions : We concluded that overnight fasting does not promote significant changes in resting and postexercise blood pressures or cardiac autonomic modulation in young men at rest (in supine and standing positions), during 30 minutes of moderate cardiorespiratory training and throughout a 30-minute postexercise recovery phase.